Perancangan Ulang Favehotel Gatot Subroto Jakarta Dengan Pendekatan Brand Identity - Thalita Haryanto, Anastasya; Salayanti, Santi; Murdowo, Djoko (eProceedings of Art & Design, 2024)
FaveHotel Gatot Subroto Jakarta is a 3-star hotel located on Jl. Gatot Subroto, Jakarta. This hotel provides rest areas for guests who travel or activities in Jakarta. Facilities offered include lobbyists, receptionists, restaurants, employee rooms, gyms, kitchens, per-type rooms, meeting rooms, and employee lockers. To improve the visitor experience, an interior redesign with the theme "Cohesion in Space Design" and the concept of "Brand Functional Alignment". This design will pay attention to elements such as floors, walls, and ceilings to create a comfortable atmosphere and fit the image of the hotel. Methods to be used include brainstorming, mid mapping, moodboard, and prototype methods. Keywords: favehotel, redesigned,brand identity, space design